2014
DOI: 10.1016/j.semarthrit.2014.05.001
|View full text |Cite
|
Sign up to set email alerts
|

The impact of rheumatoid arthritis on quality-of-life assessed using the SF-36: A systematic review and meta-analysis

Abstract: RA has a substantial impact on HRQoL. This supports recent NICE guidelines stipulating that RA patients should be regularly assessed for the impact their disease has on HRQoL and appropriate management provided.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

24
267
3
12

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 374 publications
(306 citation statements)
references
References 44 publications
24
267
3
12
Order By: Relevance
“…The past decades have shown large improvements in disease activity control of inflammatory rheumatic diseases, as shown by the large decreases in the levels of physical disability, anxiety, and depression [17]. However, the quality of life of patients with inflammatory rheumatic diseases remains considerably lower than that in the general population [13] and is comparable to that in other chronic somatic diseases including cardiovascular conditions and diabetes [1]. Thus, many patients show some level of heightened psychological distress, with a substantial percentage developing clinically relevant levels of distress, such as depression and anxiety, with prevalence rates varying between 10% and 40% depending on the criteria and instruments used (e.g., clinical interviews show lower percentages than screening questionnaires) [7,8,17e19].…”
Section: Psychological Burden Of Inflammatory Rheumatic Diseasesmentioning
confidence: 99%
“…The past decades have shown large improvements in disease activity control of inflammatory rheumatic diseases, as shown by the large decreases in the levels of physical disability, anxiety, and depression [17]. However, the quality of life of patients with inflammatory rheumatic diseases remains considerably lower than that in the general population [13] and is comparable to that in other chronic somatic diseases including cardiovascular conditions and diabetes [1]. Thus, many patients show some level of heightened psychological distress, with a substantial percentage developing clinically relevant levels of distress, such as depression and anxiety, with prevalence rates varying between 10% and 40% depending on the criteria and instruments used (e.g., clinical interviews show lower percentages than screening questionnaires) [7,8,17e19].…”
Section: Psychological Burden Of Inflammatory Rheumatic Diseasesmentioning
confidence: 99%
“…[17][18][19][20][21][22][23][24] The lower number of points in the PCS domain in comparison to the MCS domain may indicate that RA affects more the physical than the mental sphere as indicated by other authors. 21,23,24 It was also shown that the quality of life of patients with RA depends on many factors of physical, mental and social functioning sphere.…”
Section: Discussionmentioning
confidence: 99%
“…[17][18][19][20][21][22][23][24] The lower number of points in the PCS domain in comparison to the MCS domain may indicate that RA affects more the physical than the mental sphere as indicated by other authors. 21,23,24 It was also shown that the quality of life of patients with RA depends on many factors of physical, mental and social functioning sphere. 17,[19][20][21][23][24][25][26][27][28][29][30][31] Studies conducted by many authors have shown that poorer functioning of the respondents in the physical sphere is conditioned by the duration of the disease.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…C'est un concept très large qui peut être influencé de manière complexe par la santé physique du sujet, son état psychologique et son niveau d'indépendance, ses relations sociales et sa relation aux éléments essentiels de son environnement [3][4][5]. Ce concept ne cesse de se développer suscitant de plus en plus l'intérêt et l'implication des différents acteurs de la recherche dans le domaine de la santé [6][7][8]. Au Maroc, on assiste récemment à un intérêt de plus en plus grandissant pour les travaux de recherche sur la qualité de vie en Rhumatologie.…”
Section: Le Concept De « Qualite De Vie »unclassified